Identifikasi Molekuler Kutu Kebul Di Kecamatan Landasan Ulin, Kalimantan Selatan - Siti Cahaya; Dewi Fitriyanti; Muslimin S (JURNAL PROTEKSI TANAMAN TROPIKA, 2026)
Whitefly is one of the important pests in horticultural crops such as cayenne pepper that causes direct and indirect damage. Accurate identification of this species is very important in supporting the right pest control strategy. This study aims to identify the genetic diversity of whitefly that attacks cayenne pepper plants in Landasan Ulin District, South Kalimantan, using a molecular identification method based on Polymerase Chain Reaction (PCR) and genetic sequence analysis. Whitefly imago samples were collected from cayenne pepper agricultural fields, then DNA extraction, COI (Cytochrome Oxidase I) gene amplification were carried out then verification of PCR results through electrophoresis, and DNA sequencing analysis. The electrophoresis results showed that the amplified DNA band was in the range of ~700 bp. The results of BLAST analysis showed that the whitefly sample from Landasan Ulin had a 100% similarity level with B. tabaci isolates of biotype Asia I from India and Vietnam and was genetically different from B. tabaci populations in other regions in Indonesia even though they were classified as the same biotype, and different from other biotypes such as MEAM1 (B), MED (Q), SSA1, and SSA2. Thus, it can be concluded that the whitefly that attacks cayenne pepper in Landasan Ulin District belongs to the biotype Asia I, which has significant genetic differences with populations from other regions in Indonesia.